Computational analysis of collagenase from different Vibrio, Clostridium and Bacillus strains to find new enzyme sources - Navid Nezafat; Manica Negahdaripour; Ahmad Gholami; Younes Ghasemi (Shiraz University of Medical Sciences, 2015)
Collagenase is one the important enzyme, which is applied in varied fields ranging from tannery, food and cosmetic industries to clinical therapies. Currently, the commercially available collagenase enzyme has been produced by Clostridium histolyticum bacteria. In our study, in order to find new sources of collagenase producer, 30 collagenases from different species of Clostridium, Vibrio and Bacillus were evaluated from the view of phylogenetic relation, domain architecture and physiochemical features. Totally our results indicate that the non-pathogenic C. novyi (NT) with the aliphatic index (80.68), instability index (27), pI (6.54), Mw (112.838 kDa) and two PPC domain could be suggested as a potent bacteria for industrial production of collagenase.